- #1

- 191

- 3

## Homework Statement

The fundamental equation of a system of [itex]\tidle{N}[/itex] atoms each of which can exist an atomic state with energy [itex]e_u[/itex] or in atomic state [itex]e_d[/itex] (and in no other state) is

[tex]

F= - \tilde{N} k_B T \log ( e^{-\beta e_u} + e^{-\beta e_d} )

[/tex]

Here [itex]k_B[/itex] is Boltzmann's constant [itex]\beta = 1/k_BT[/itex]. Show that the fundamental equation of this system, in entropy representation, is

[tex]

S = NR \log \left (\frac{1+Y^{e_d/e_u}}{Y^Y} \right)

[/tex]

where

[tex]

Y= \frac{U-\tilde{N}e_u}{\tilde{N}e_d-U}

[/tex]

Hint: introduce [itex] \beta =1/k_BT[/itex] and show that [itex]U = F + \beta \partial F / \partial \beta = \partial ( \beta F) /\partial \beta [/itex]. Also, for definiteness, assume [itex] e_u < e_d[/itex] and note that [itex]\tilde{N}k_B = NR[/itex].

## Homework Equations

[tex]

S = -\partial F / \partial T = -(\partial F /\partial \beta )(\partial \beta /\partial T) = (\partial F / \partial \beta)( \beta /T)

[/tex]

## The Attempt at a Solution

I showed the hint but will not write out the solution here. Then we have

[tex]

U = \partial ( \beta F) /\partial \beta = \tilde{N} \frac{e_u e^{-\beta e_u} + e_d e^{-\beta e_d}}{ e^{-\beta e_u} + e^{-\beta e_d}}[/tex]

from which I get [itex]

e^{\beta( e_u - e_d)} = Y [/itex].

Also,

[tex]

S = \tilde{N}k_B \log ( e^{-\beta e_u} + e^{-\beta e_d} ) +\tilde{N} \beta k_B \frac{e_u e^{-\beta e_u} + e_d e^{-\beta e_d}}{ e^{-\beta e_u} + e^{-\beta e_d}}

[/tex]

which I rewrote as

[tex]

NR\log (1+Y) - NR\beta e_u + NR \beta \frac{e_u +e_d Y}{1+Y} = NR \log (1+Y)+ NR \beta \frac{Y(e_d-e_u)}{1+Y} = NR \log (1+Y) - NR \frac{Y}{Y+1} \log Y = NR \log \left ( \frac{1+Y}{Y^{Y/Y+1}} \right)

[/tex]

which is not (at least obviously) the same, but I cannot see my mistake. Help would be appreciated.